A Novel RNF216 Variant Causing Gordon Holmes Syndrome in Three Lithuanian Siblings - Karlonaitė, Melita; Kanapickaitė, Ugnė; Laukienė, Romena; Utkus, Algirdas; Burnytė, Birutė (Acta medica Lituanica, 2026)
Background: Gordon Holmes syndrome (GHS) is a rare genetic disorder, usually manifesting as a broad spectrum of neurological symptoms and hypogonadotropic hypogonadism. Only a limited number of cases presenting this congenital disorder have been reported in the literature. Since the genetic and phenotypic heterogeneity of GHS, it is crucial to report novel cases. Case presentation: Here we report a novel homozygous missense variant in RNF216 gene c.1055T>G (p.(Phe352Cys)) in three siblings. Primary concerns were absence of secondary sexual characteristics, and amenorrhea occurred among female patients. Based on laboratory test results and clinical features, hypogonadotropic hypogonadism was diagnosed. Neurological examination revealed no signs of ataxia in siblings. However, brain magnetic resonance imaging revealed pronounced changes in the cerebral white matter for female patients. Due to primary amenorrhea and the absence of secondary sexual characteristics, treatment was initiated. Treatment might be adjusted in the presence of fertility considerations. Conclusions: This case contributes to the limited knowledge of GHS and highlights the importance of hypogonadotropic hypogonadism treatment and close observation of neurological symptoms that may develop over time.